Handbook of Comparative Criminal Law [Book review] - CHEN, Siyuan (Institutional Knowledge at Singapore Management University, 2011)
Imagine gathering the views of some of the leading criminal law academics from around the world – traversing 16 countries, 6 continents, and 5 different legal systems, to be precise – by way of essays designed to provide an introductory framework for almost all of the major criminal law systems in the world to be compared and contrasted. This 660-page book is supposed to be a compelling manifestation of that imagination, and indeed is touted as a first of its kind in terms of the depth and breadth in coverage.